Explaining the Factors Related to the Enrichment of Marriage in the Marriage Contract Stage: A Grounded Theory Study - Goudarzi, Maryam; keshavarz Afshar, Hossein; Aslani, Khaled; Salehi, Keyvan (Psychology of Woman Journal, 2025)
Objective:This study aimed to analyze the factors influencing the enrichment of couples’ relationships during the Marriage Contract Stage—a period in Iranian culture following the formal marriage contract, known as the "Aghd" ceremony, where couples are legally married but have not yet held their wedding celebration. Methods and Materials: The research employed a qualitative methodology using grounded theory. The study sample comprised engaged couples living in Tehran. Participant selection continued until theoretical saturation was reached, resulting in a total of 11 paired interviews (22 individual interviews). Data collection was conducted through semi-structured individual interviews, and the data were analyzed using the three-step coding process—open, axial, and selective coding—based on the method proposed by Corbin and Strauss . Findings:The analysis identified 105 primary codes, which were organized into 14 subcategories: self-esteem, expressing intimacy and empathy, creating shared meaning, love, sincere communication patterns, recognizing each other’s needs, compatibility, resolving marital conflicts, compromising styles, acceptance of responsibility, non-acceptance and accountability, non-forgiveness, self-management, and relationship management. These subcategories were further grouped into 5 main categories. Overall, the findings suggest that the enrichment of marriage during the Marriage Contract Stage is not spontaneous or unilateral; rather, it is influenced by multiple factors that can either enhance or diminish the quality of life for couples. Conclusion: Marital enrichment requires mutual effort to maintain and improve the relationship.